Laboratory manual for applied botany - Levetin, Estelle (McGraw-Hill, 2002)
Science education is experiencing a revitalization, as it is recognized that science should be accessible to everyone, not just society's future scientists. One way to make the study of science more substantive to the non-major is to require a laboratory component for all science courses. The subject of applied botany with its emphasis on the practical aspects of plant science, the authors believe, will be appealing to the non-major as it exemplifies how a basic science can be applied to problem solving. Laboratory Manual for Applied Botany will make students realize that the study of plants is relevant to their lives and that they can participate in the discovery process of science.